Cost analysis for optimum thicknesses and environmental impacts of different insulation materials - Ozel, Meral (Elsevier Science Sa, 2012)
In this study, the optimum thickness of thermal insulation used to reduce heat gain and losses in buildings is investigated under dynamic thermal conditions by using the climatic conditions of Elazig, Turkey. Numerical method based on an implicit finite difference procedure which has been previously validated is used to determine yearly cooling and heating transmission loads, yearly averaged time lag and decrement factor under steady periodic conditions. These loads are used as inputs to an economic model for the determination of the optimum insulation thickness. The optimum insulation thicknesses, energy savings and payback periods are calculated by using life-cycle cost analysis over lifetime of 20 years of the building. Results show that the optimum insulation thicknesses vary between 5.4 and 19.2 cm, energy savings vary between 86.26 and 146.05 $/m(2), and payback periods vary between 3.56 and 8.85 years for different insulation materials. The environmental impacts of thermal insulation are also investigated. It is seen that by applying optimum insulation thickness in uninsulated wall, yearly fuel consumption and emissions are decreased by 68-89.5% depending on insulation materials. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Insulation materials; Yearly heating and cooling loads; Optimum insulation thickness; Energy savings; Fuel consumption and emissions